18.3: Flexible Barrier Technology for Enabling Rollable AMOLED Displays and Upscaling Flexible OLED Lighting. Issue 1 (1st July 2013) - Li, Flora M.; Unnikrishnan, Sandeep; van de Weijer, Peter; van Assche, Ferdie; Shen, Jie; Ellis, Tim; Manders, Wiel; Akkerman, Hylke; Bouten, Piet; van Mol, Ton
Abstract: The availability of a high performance thin‐film barrier is the most critical challenge in upscaling and commercializing flexible OLED products. We report a flexible thin‐film‐barrier technology that meets lifetime specifications for OLED lighting, and demonstrate it in rollable QVGA a‐IGZO AMOLED displays. Roll‐to‐roll manufacturing of this high performance barrier film will be presented.